2019
DOI: 10.1097/sla.0000000000003737
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Statin Use and 90-Day Mortality After Noncardiac Surgery

Abstract: Objective: The aim of this study was to investigate the association between preadmission statin use and 90-day mortality after planned elective noncardiac surgery in adult patients. Summary Background Data: Statin therapy is known to have pleiotropic effects, which improve the outcomes of various diseases. However, the effect of perioperative statin therapy on postoperative mortality remains controversial. Methods: This retrospective cohort study analyzed the medical records of adult patients who were admitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Fourth, the use of statins was associated with a reduced risk of MACE within 120 days with a weighted hazard ratio in patients with statin therapy of 0.59 (95% CI 0.41 to 0.86). This important observation strengthens prior studies suggesting a possible reduction of long-term cardiac complications by statins 17–20,40 . A meta-analysis of 12 rather small randomised controlled trials overall involving 4707 patients undergoing noncardiac surgery showed a neutral effect on all-cause and cardiovascular mortality but a reduction in MI during follow-up (OR 0.46) in patients treated with statins compared with the control group 19 .…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Fourth, the use of statins was associated with a reduced risk of MACE within 120 days with a weighted hazard ratio in patients with statin therapy of 0.59 (95% CI 0.41 to 0.86). This important observation strengthens prior studies suggesting a possible reduction of long-term cardiac complications by statins 17–20,40 . A meta-analysis of 12 rather small randomised controlled trials overall involving 4707 patients undergoing noncardiac surgery showed a neutral effect on all-cause and cardiovascular mortality but a reduction in MI during follow-up (OR 0.46) in patients treated with statins compared with the control group 19 .…”
Section: Discussionsupporting
confidence: 81%
“…In a large prospective cohort study, the use of statins was associated with a reduction in all-cause mortality; RR was 0.58 and for cardiovascular mortality 0.42 20 . Another retrospective cohort study found a positive effect of statin therapy on 90-day mortality (OR 0.74) 40 . In our cohort, the ARR of 1.7% would indicate a NNT of 59 for events within 120 days.…”
Section: Discussionmentioning
confidence: 41%
See 2 more Smart Citations
“…With great interest, we read the retrospective cohort study by Im et al, 1 which evaluated the association between preoperative statin use and intermediate-term survival after noncardiac surgery. They performed statistical analyses in a robust and sophisticated manner with sensitivity analyses.…”
mentioning
confidence: 99%